2015
DOI: 10.1155/2015/206325
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Benzimidazolium Salicylate: NLO Property from a Centrosymmetric Crystal

Abstract: A new organic charge transfer molecular complex salt of benzimidazolium salicylate (BSL) single crystals was grown by the slow evaporation solution growth technique using methanol as a solvent at room temperature. The grown crystals were characterised by single crystal X-ray diffraction (XRD) which confirms that the crystal belongs to monoclinic system with the centrosymmetric space group P2 1 / . The crystalline perfection of the grown crystal was analyzed by high resolution X-ray diffraction (HRXRD). The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 36 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…This requires uncomplicated equipment (Dufresne, 2021) and is recommended by the International Tables for Crystallography (Klapper & Hahn, 2006 (Inbaseelan et al, 2016). With benzimidazolium salicylate, the piezoelectric resonance recorded at 10 KHz matched the vibrational frequency of the crystal (Amudha et al, 2015). In view of the piezoelectric outcome, the space groups of these two salts are better regarded as ones of lower symmetry.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This requires uncomplicated equipment (Dufresne, 2021) and is recommended by the International Tables for Crystallography (Klapper & Hahn, 2006 (Inbaseelan et al, 2016). With benzimidazolium salicylate, the piezoelectric resonance recorded at 10 KHz matched the vibrational frequency of the crystal (Amudha et al, 2015). In view of the piezoelectric outcome, the space groups of these two salts are better regarded as ones of lower symmetry.…”
Section: Discussionmentioning
confidence: 96%
“…A test on a crystalline specimen of [Cu(H 2 O) 4 (C 2 H 5 NO 2 ) 2 ]Á2C 6 H 2 N 3 O 7 Á2H 2 O gave a positive outcome (Inbaseelan et al, 2016). With benzimidazolium salicylate, the piezoelectric resonance recorded at 10 KHz matched the vibrational frequency of the crystal (Amudha et al, 2015). In view of the piezoelectric outcome, the space groups of these two salts are better regarded as ones of lower symmetry.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Organically based NLO materials offer several advantages over inorganic systems, including high electronic susceptibility, high molecular polarizability and fast response time [12]. Although noncentrosymmetric crystals have found application as NLO materials, there are also a few reports where centrosymmetric crystals have been shown to possess NLO properties [12][13][14][15]. In recent years, BA/TBA-based derivatives have also been studied as NLO materials as they hold both hydrogen bond donors and acceptors, a feature that makes them suitable as crystal engineering materials with specific programmed properties [7,12,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The title compound, Benzimidazolium is one such π-donoracceptor molecular compound; it can receive a donor (H + ) form salicylic acid. Previously, Amudha et al, [16] reported the crystal structure of Benzimidazolium Salicylate and also SHG conversion efficiency determined by Kurtz's Perry technique [17]. Jeyaram et al has studied about the BISA for exploitation towards the NLO application below 118C [18].…”
Section: Introductionmentioning
confidence: 99%